A double-blind randomised placebo-controlled trial of melatonin as an adjuvant agent in induction of labour (MILO): a study protocol. Issue 2 (12th February 2020) - Swarnamani, Kamala; Davies-Tuck, Miranda; Wallace, Euan; Mol, Ben W; Mockler, Joanne
Abstract : Introduction: Induction of labour (IOL) is a common practice. In Australia, up to 40% of women undergoing labour induction will ultimately have a caesarean section. As a biological role for melatonin in the onset and progress of labour has been demonstrated, we aim to test the hypothesis that addition of melatonin will reduce the need for caesarean section. Methods and analysis: This is a double-blind, randomised, placebo-controlled trial in women undergoing IOL at term. We plan to randomise 722 women (1:1 ratio) to receive either melatonin (four doses of 10 mg melatonin: first dose—in the evening at the time of cervical balloon or Dinoprostone PGE2 vaginal pessary insertion, second dose—at time of oxytocin infusion commencement, third dose—6 hours after the second dose, fourth dose—6 hours after the third dose) or placebo (same dosing regime). Participants who are having artificial rupture of the membranes only as the primary means of labour induction will receive up to three doses of the trial intervention. The primary outcome measure will be the requirement for a caesarean section. Secondary outcomes will include duration of each stage of labour and time from induction to birth, total dose of oxytocin administration, epidural rate, indication for caesarean section, rate of instrumental deliveries, birth within 24 hours of induction commencement, estimated blood loss, Apgar score at 5 min, neonatal intensive care unit admissions and participant satisfaction. Maternal melatonin levels will be measured immediately before commencement of the oxytocin intravenous infusion and 3 hours after and at the time of birth in order to determine any differences between the two trial arms. Ethics and dissemination: The study is conducted in accordance with the conditions of Monash Health HREC (RES-17-0000-168A). Findings from the trial will be disseminated through peer-reviewed publications and conference presentations. Protocol version: V.7.0, 30 July 2019. Trial registration number: ACTRN12616000311459, Universal trial number: (UTN) U1111-1195-3515.